The Relationship Between Physical Activity and Student Academic Performance on Online Learning During the Covid-19 Pandemic - Nury Nabila Risky; Tri Laksono; Prihantoro Larasati Mustiko (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
This research is expected to find out the relationship between physical activity and academic performance of students during online learning during the Covid-19 pandemic. This research is a scientific review research (non trial) with a Cross Sectional approach methodology. Sampling of this research by purposive sampling method. totaling 154 students (n=154). Data collection using IPAQ and SCLS questionnaires. In analyzing the data here, the univariate and bivariate frequency tests are used. The normality test used the Kolmogorov Smirnov test and the correlation test used the Rank Spearman test. Based on the correlation test results with the Sperman Rho test, a significance value (p) of 0.037 (p < 0.05) was obtained, which means that there is a relationship between physical activity and academic performance with a value of r = 0.168* which is correct, meaning that there is a fairly weak relationship. but in a positive direction.